Detection of the nearest Jupiter analogue in radial velocity and astrometry data. Issue 4 (21st October 2019) - Feng, Fabo; Anglada-Escudé, Guillem; Tuomi, Mikko; Jones, Hugh R A; Chanamé, Julio; Butler, Paul R; Janson, Markus
ABSTRACT: The presence of Jupiter is crucial to the architecture of the Solar system and models underline this to be a generic feature of planetary systems. We find the detection of the difference between the position and motion recorded by the contemporary astrometric satellite Gaia and its precursor Hipparcos can be used to discover Jupiter-like planets. We illustrate how observations of the nearby star ϵ Indi A giving astrometric and radial velocity data can be used to independently find the orbit of its suspected companion. The radial velocity and astrometric data provide complementary detections which allow for a much stronger solution than either technique would provide individually. We quantify ϵ Indi A b as the closest Jupiter-like exoplanet with a mass of 3 M Jup on a slightly eccentric orbit with an orbital period of 45 yr. While other long-period exoplanets have been discovered, ϵ Indi A b provides a well-constrained mass and along with the well-studied brown dwarf binary in orbit around ϵ Indi A means that the system provides a benchmark case for our understanding of the formation of gas giant planets and brown dwarfs.